Investigation of TSDC and dielectric modulus of PVDF–BaZrO3 nanocomposites thin film. (October 2018) - Sagar, Rohan; Gaur, M.S.; Bhadoria, B.S.
Abstract: The polyvinylidene fluoride (PVDF) - barium zirconate (BaZrO3 ) nanocomposite samples were prepared by varying BaZrO3 contents (i.e. 1, 3 and 5% by weight) using solution mixing method. PVDF, filled with well dispersed functionalized BaZrO3 nanoparticles. The surface structure of nanocomposite samples were carried out by Atomic Force Microscopy (AFM). Surface roughness of samples was increases with increasing BaZrO3 concentration, while the average diameter of NPs was almost unaffected. The contact angle of PVDF samples with water (i.e. 89°) is larger than contact angle of PVDF samples with IM-diiodomethane (55°). The contact angle is measured by the sessile drop method with respect to polar liquid (i.e. water and IM-diiodomethane) to understand the interaction of BaZrO3 nanoparticles into the surface of PVDF and PVDF nanococomposite samples. The study of contact angle showed that an improvement of hydrophobicity of PVDF samples with increasing concentration of BaZrO3 NPs. In most of the observations the mainly three thermally stimulated discharge current (TSDC) peaks were observed in PVDF and PVDF–BaZrO3 nanocomposites samples. The TSDC peaks are attributed due to α, β and γ phase of PVDF. Further, the origin of TSDC peaks were correlated with results obtained from impedance spectroscopy. Highlights: BaZrO3 nanoparticles in PVDF matrix influences the surface and bulk properties. Atomic Force Microscopy demonstrates the surface morphology of PVDF-BaZrO3 nanocomposite. The presence of α, β and γ phase are confirmed by TSDC. Three relaxation processes in TSDC are correlated with relaxation process in dielectric modulus. Contact angle gives the surface free energy and its correlation with structural and electrical properties.